(3aj SHjd GdJGL (B/s - (3GdefadhWj , eUWai dWajs; (3bGSe, QjGV s ((3HjQhJ (B:s (3eDSSI HMShf (B:s (3OGQ GdefGd,s, 2001)
(3eCSGI TYQjI JQJOj KhH bUI, JeGRL ajgG GdhGbY HGdNjGd, aHOJ QGFYI COHjI, eVehfgG CNdGbj, hHWdgG aJi JYGQVJ aj faSg YGWaJGf bhjJGf (B: (3MH GdCSQI hMH GdhWf, aVMi HGdChdi aOGA ddKGfjI, Ke VMi MjGJg aOGA dTQa GdCSQI(B.s
(3cJH gPG GdYed GdCOHj GdTGYQ GdaQfSj aQGfShG chHjg aj GdYGe (B1895 (3LGYdG EjGg aj bGdH eSQMj TYQj hbO LYdg GdefadhWj aj QhGjI eMhdG GdMhGQ Edi SQO fKQj jNVY dCSdhHg GdNGU s
Keywords: (3chHjg , aQGfShG s -- (3aQfSG s; (3GdbUU GdaQfSjIs -- (3bQf (B19s